Does Sensory Retraining Improve Sensation and Sensorimotor Function Following Stroke: A Systematic Review and Meta-Analysis - Serrada, Ines; Hordacre, Brenton; Hillier, Susan L. (Frontiers in Neuroscience, 2019)
Abstract Background/ To investigate sensory-based interventions reported in the literature and determine the effectiveness to improve sensation and sensorimotor function of individuals following stroke. Methods/ Electronic databases and trial registries were searched from inception until November 2018, in addition to hand searching systematic reviews. Study selection included randomised controlled trials for adults of any stroke type with an upper and/or limb sensorimotor impairment. Participants all received a sensory-based intervention designed to improve activity levels or impairment, which could be compared with usual care, sham, or another intervention. Two reviewers independently assessed eligibility of full texts and methodological quality of included studies was assessed using the Cochrane Risk of Bias Tool. Results/ A total of 38 study trials were included (n=1093 participants); 29 explored passive sensory training, 6 active and 3 hybrid. Meta-analyses (13 comparisons) demonstrated a moderate effect in favour of passive sensory training. Narrative syntheses were completed for studies unable to be pooled due to heterogeneity of measures or insufficient data. Conclusions/ Findings from the meta-analyses and single studies highlight some support for the effectiveness of passive sensory training in relation to sensory impairment and motor function. However, evidence for active sensory training continues to be limited. Further high-quality research with rigorous methods (adequately powered with consistent outcome measures) is required to determine the effectiveness of sensory retraining in stroke rehabilitation, particularly for active sensory training.